Penilaian Ranah Psikomotor Dalam Pembelajaran Bahasa Arab - Muhamad Fauzan Halim; Muhamad Fauzan Halim1, Husnaini Muhammad Makhluf; Raswan; Ubaid Ridho (Educational Journal, 2026)
This study aims to describe and analyze students' psychomotor skills in Arabic language learning. The method used is descriptive qualitative, with data sources consisting of books and journal articles relevant to assessing the psychomotor domain in Arabic language learning. The research focuses on analyzing students' observable behavior, acting abilities, and language skills. The approach used is pedagogical-linguistic, emphasizing the relationship between language learning theory and the application of psychomotor skills across the four language domains (listening, speaking, reading, and writing). The results indicate that the psychomotor domain reflects students' ability to practice Arabic through Simpson's seven skill levels: perception, readiness, guided movement, mechanism, complex movement, adaptation, and origination. Assessment instruments used include worksheets, direct observation, and student portfolios. Therefore, psychomotor domain assessment plays a crucial role in assessing students' success in mastering Arabic language skills actively, communicatively, and applicably.